STRATEGI KOMUNIKASI PEMASARAN NUVANTARA TRAVEL SEBAGAI UPAYA PARIWISATA SEHAT DI MASA PANDEMI COVID 19 - Rezalina, Ayu Rezalina; Setianingrum, Vinda Maya (The Commercium, 2024)
The Covid-19 pandemic that has hit the world since mid-2020 has forced the tourism industry to adapt by implementing the concept of healthy tourism in the hope that this adaptation can restore public trust in the tourism industry. This research aims to understand the marketing communication strategies carried out by Nuvantara as a travel service provider that implements healthy tourism. Data was collected through the interview method with the Nuvantara team. Data analysis was carried out in four stages by Miles and Huberman. The research results show that Nuvantara applies the concept of healthy tourism with a holistic CHSE (cleanliness, health, safety and environment) approach. Nuvantara's marketing communication strategy is carried out with the help of three main channels, namely Instagram as the channel most accessed by the public, WhatsApp as a two-way communication channel, and Notion as a source of specific information that can be accessed. Furthermore, Nuvantara's electronic word of mouth (EWOM) occurs naturally because of the positive experiences that consumers experience when using Nuvantara's services.